Ophthalmological findings in children and young adults with genetically verified mitochondrial disease. Issue 1 (21st December 2009) - Grönlund, M A; Honarvar, A K Seyedi; Andersson, S; Moslemi, A R; Oldfors, A; Holme, E; Tulinius, M; Darin, N
Abstract : Aim: To describe ophthalmological phenotypes in patients with mitochondrial disease and known genotypes. Methods: A retrospective study was performed on 59 patients (29 male, 30 female) with a mean age of 11.8 years who had mitochondrial disease with known DNA mutations. Fifty-seven of the 59 subjects underwent a detailed ophthalmological examination including visual acuity (VA), eye motility, refraction, slit-lamp examination, ophthalmoscopy and, in almost one-half of the cases, a full-field electroretinogram (ERG). Results: Forty-six (81%) of the patients had one or more ophthalmological findings such as ptosis (n = 16), reduced eye motility (n = 22) including severe external ophthalmoplegia (n = 9), strabismus (n = 4), nystagmus (n = 9), low VA (n = 21), refractive errors (n = 26), photophobia (n = 4), and partial or total optic atrophy (n = 25). Pigmentation in the macula and/or periphery was noted in 16 patients. In 10/27 investigated individuals with full field ERG, retinal dystrophy was recorded in six different genotypes representing Kearns–Sayre syndrome (n = 5), Leigh syndrome (n = 1), Mitochondrial encephalopathy, lactic acidosis, and stroke-like episodes (MELAS) (n = 1), Myoclonus epilepsy with red ragged fibres (MERRF) (n = 1), Leber hereditary optic neuropathy (n = 1) and mitochondrial myopathy (n = 1). Conclusion: The results show that a majority of patients with mitochondrial disorders have ophthalmological abnormalities. We recommend that an ophthalmological examination, including ERG, be performed on all children and adolescents who are suspected of having a mitochondrial disease.